Quo vadis, realisme? O obecnym stanie sporu o realizm naukowy - Kotowski, Mateusz (Filozofia Nauki, 2018)
The article investigates the intuition that both scientific realism and scientific antirealism are turning into degenerating research programs. The evolution of realism in reaction to pessimistic (meta)induction has certainly led to its increased sophistication as it has given rise to various versions of selective realism. However, many current discussions seem either too focused on semantic niceties or are turning into endless quarrels over case-study refutations of particular forms of realism. The point of finding a better understanding of the relations of scientific knowledge to the world seems to get lost in the process. Magnus, Callender, and Saatsi are among those who see the problem. Although drawing on different observations, they agree that the source of the problem is the wholesale approach according to which it is possible to resolve the realism debate in one move, by finding a single universal method of interpreting any scientific theory. Instead, they call for a more modest approach, based on case-by-case analyses. Particularly promising is Saatsi’s idea of exemplar realism, according to which realism should be an attitude motivating detailed case studies rather than a specific account of science in general.